Accomplishment report for the intensive community nursing experience in Poblacion V, Alfonso, Cavite - Ferrer, Christianna Joy F.; Tegrado, Lindsay Allen R. (Manila College of Nursing, University of the Philippines Manila, 2017)
This accomplishment report encompasses the different phases of the nursing process implemented in a community setting, Poblacion V, Alfonso, Cavite. the assessment phase includes different assessment methods to objectively measure the health status, behaviors, and attitudes of the barangay. It comprises of the rapid appraisal of the barangay; utilizing ocular survey, key informant interviews, and review of records as sources of data. In addition to this, the student nurses also conducted comprehensive house-to-house survey from January 2017 to May 2017 to verify and gather household and individual data. The diagnostic phase includes arriving to the health problems in the community deduced by the cues obtained from the assessment phase and prioritization of the determined problems with the help of the barangay officials. As for the planning phase, it includes planning together with the barangay to come up with the health programs appropriate and feasible based on the resources available in the community. The formulated programs will be used to address the problems and would help improve the population's health status. Subsequently, the implementation phase encompasses the different health programs and services that stemmed from the planning phase. The health programs and services that stemmed from the planning phase. The health programs were implemented in cooperation and participation of the residents of the community. Lastly, the process of evaluation was undertaken in order to guage the effect of the implemented health programs and services.
Introduction -- Objectives -- Scope and limitations -- Methodology --Rapid appraisal -- PhilPEN update -- Program development and implementation -- Process evaluation -- Other related activities -- References -- Appendix
Includes bibliographies
In cooperation with the residents of Poblacion V and with the support of the Barangay Council lead by Hon. Isagani D. Ronsairo
Keywords: Intensive community experience